Unusual case of laryngeal foreign body - Ganguly, SN; Reddy, NS; Shrestha, A; Shah, D; Shakya, N; Acharya, S (Journal of College of Medical Sciences-Nepal, 2010)
The foreign bodies in respiratory tract have been major cause of morbidity and present as challenge to otolaryngologist. The spectrum of presentation varies widely from sudden death due to respiratory obstruction to accidental finding during routine investigation. One case of unusual presentation of laryngeal foreign body with loss of voice is described here. Key words: Respiratory obstruction laryngeal; foreign body DOI: 10.3126/jcmsn.v6i1.3601 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 44-46